Penerapan Foot & Hand Massage Pada Asuhan Keperawatan Post Partum Sectio caesarea Atas Indikasi Ketuban Pecah Dini - Gisa Miftahul Balkis; Ira Sukyati (AKPER Pasar Rebo, 2023)
Premature rupture of membranes is the rupture of the membranes before actual labour, with or without contractions. According to WHO (2014) the incidence of premature rupture of membranes ranges from 5-10% of all births. KPD occupies the 4th position out of 10 cases of caesarean delivery at Pasar Rebo Hospital, Jakarta. The purpose of doing a case study is to find out more deeply about the nursing problems that arise so as to be able to make the right planning. Methods of data collection by interviews, observation, physical examination, and diagnostic examination. The population in this study were patients named NY. N is 34 years old with post partum sectio caesarea for indications of premature rupture of membranes at Pasar Rebo Hospital, Jakarta on March 20-22 2022. The results of nursing care and implementation obtained the conclusion that foot & hand massage has not been proven as a whole in reducing the intensity of the pain scale in post SC mother. It is hoped that the results of this study can provide information for hospitals and educational institutions regarding nursing care and its application in patients.